THE USE OF CHATGPT TO IMPROVE SPEAKING SKILLS - Amrina Amrina; Dinda Alifia Salsabi; Krim Ulwi (Yayasan Adra Karima Hubbi, 2026)
Media play a major role as a means of learning various skills for students. One of these is speaking skill, and improving speaking skill is an important aspect that can support proficiency in communication. ChatGPT is one medium designed to understand and respond to voice messages in various foreign languages. This study aimed to determine the benefits of ChatGPT in improving speaking skills. The study employed a quantitative research method, with data collected through interviews and questionnaire tests. The findings showed that students could use ChatGPT to improve their speaking skills, as demonstrated by the finding that 80% of the students achieved the highest scores. The study concluded that using ChatGPT provides many benefits for improving speaking skills, including helping students learn new vocabulary and explore appropriate ways of using language. This study was limited to speaking skills, although many other skills can also be improved through the use of ChatGPT. Future researchers are expected to investigate the use of ChatGPT to improve other skills and to produce different conclusions. This study also recommends that future researchers use it as a reference when conducting research on improving speaking skills through ChatGPT.